2022
DOI: 10.1155/2022/5009289
|View full text |Cite
|
Sign up to set email alerts
|

Sacubitril Valsartan Enhances Cardiac Function and Alleviates Myocardial Infarction in Rats through a SUV39H1/SPP1 Axis

Abstract: Sacubitril valsartan (lcz696) has been demonstrated as a substitute for angiotensin-converting enzyme inhibitors and angiotensin receptor blockers for the treatment of heart failure. This research is aimed at examining the effects of lcz696 and its target molecules on myocardial infarction (MI). A rat model of MI was induced by left anterior descending artery ligation and treated with lcz696. Lcz696 treatment significantly reduced cardiac injury and heart failure, restored the left ventricular fractional short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…S/V effectively ameliorates symptoms in patients with chronic HF and AMI ( 6 , 7 , 26 ). In rats, S/V results in a marked improvement in cardiac function and reductions in oxidative stress and inflammatory processes following MI ( 27 ). Large clinical studies have shown that SGLT2i decreases in the incidence of cardiovascular deaths and HF hospitalizations in patients with chronic HF ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…S/V effectively ameliorates symptoms in patients with chronic HF and AMI ( 6 , 7 , 26 ). In rats, S/V results in a marked improvement in cardiac function and reductions in oxidative stress and inflammatory processes following MI ( 27 ). Large clinical studies have shown that SGLT2i decreases in the incidence of cardiovascular deaths and HF hospitalizations in patients with chronic HF ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…HDAC2 silencing affects the mRNA levels of calcium-activated potassium channels, resulting in delayed repolarization and prolonged action potentials [ 84 ]. Silencing of the HMT SUV39H1 can block the protective effect of sacubitril/valsartan on myocardial injury and heart failure after myocardial infarction [ 85 ]. SUV39H1 can bind to the promoter of the HDAC SIRT1 to inhibit its transcription of SIRT1, ultimately exacerbating the decline in cardiac function after ischemia–reperfusion injury.…”
Section: Role Of Chromatin Modifiers In Human Diseasesmentioning
confidence: 99%
“…Notably, SPP1's association with cancer is profound, with its pivotal role in tumor invasion, metastasis, apoptosis, and angiogenesis documented extensively [4][5][6][7]. Shedding light on its significance in cardiovascular health, studies by Shen et al reveal that suppressing SPP1 leads to improvements in cardiac function, prevention of cardiac remodeling, reduction in oxidative stress and inflammation, and inhibition of cardiomyocyte apoptosis [8]. Recent investigations have also underscored the importance of SPP1, a cytokine, in the retina and optic nerve head.…”
Section: Introductionmentioning
confidence: 99%